2014
DOI: 10.1386/tmsd.13.2.135_1
|View full text |Cite
|
Sign up to set email alerts
|

Examining consumer acceptance of green innovations using innovation characteristics: A conceptual approach

Abstract: In the wake of global warming and environmental preservation, all processes and actions are now being directed along the lines of creating a greener environment. Household solar equipments are one such initiative, whereby people around the world are being encouraged to adopt green innovations even within homes. Recent emphasis is particularly along the usage of solar energy for home lighting, heating, and cooking. To achieve increased adoption of these green innovations, it is important to understand the behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 96 publications
1
7
0
Order By: Relevance
“…This finding accords with that of Claudy et al (2011) in Ireland and Chou et al (2012) in Taiwan, who reported a significant influence of observability in influencing the purchasing of solar products. Their findings were also validated by Kapoor et al ((2014)) in similar studies conducted in Swansea (United Kingdom) on household solar equipment.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…This finding accords with that of Claudy et al (2011) in Ireland and Chou et al (2012) in Taiwan, who reported a significant influence of observability in influencing the purchasing of solar products. Their findings were also validated by Kapoor et al ((2014)) in similar studies conducted in Swansea (United Kingdom) on household solar equipment.…”
Section: Discussionsupporting
confidence: 61%
“…The questionnaire was adapted from scales that had previously been validated from previous studies (refer to annexure 1). "Relative advantage", "complexity", "compatibility" and "observability" were measured using items which were adapted from Rogers (2003), Chou et al (2012), Alam et al (2014), and Kapoor et al ((2014)). For "attitudes", "subjective norm", "perceived behavioural control", "behaviour intention" and "adoption behaviour", the items used were adapted from Wang et al (2016), Moser (2015), M.F.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Scales from previous studies were adapted to measure the constructs in this study. The following sources were used: functional value (Biswas & Roy, 2015a;Malhotra & Maheshwari, 2011); social value (Lorek & Fuchs, 2013;Zhao et al, 2014); emotional value (Suki & Suki, 2015); conditional value (Wang et al, 2013); epistemic value (Kaufmann et al, 2012;Mostafa, 2009); relative advantage (Dalton et al, 2008;Rogers, 2003); compatibility (Ozaki & Sevastyanova, 2011;Rogers, 2003); complexity (Arkesteijn & Oerlemans, 2005;Chou et al, 2012); observability (Kapoor et al, 2014); attitudes (Zhou et al, 2013); PBC (Moser, 2015); behavioral intention (Wu & Chen, 2014), and actual adoption behavior (Ha & Janda, 2012;Kim et al, 2013). All of the constructs were measured using a 7point Likert scale ranging from 1 ¼ strongly disagree to 7 ¼ strongly agree.…”
Section: Measurement Instrumentmentioning
confidence: 99%